Ultrasonic velocity and elastic anomaly in charge-ordered Nd₀.₅Ca₀.₅Mn₁₋ₓCrₓO₃, Nd₀.₃La₀.₂Ca₀.₅₋ᵧSrᵧMnO₃ and Dy₀.₅₋zErzBa₀.₅CoO₃ magnetic ceramics / Suhadir Shamsuddin - Shamsuddin, Suhadir (Institute of Graduate Studies, UiTM, 2015)
Three series of charge-ordered compounds Nd0.5Ca0.5Mn1-xCrxO3 (NCMCO) (0≤x≤0.05), Nd₀.₃La₀.₂Ca₀.₅₋ᵧSrᵧMnO₃ (NLCSMO) (0≤y≤0.05) and Dy₀.₅₋zErzBa₀.₅CoO₃ (DEBCO) (0≤z≤0.05) ceramics were prepared using the solid-state reaction method. For NCMCO series, resistivity and susceptibility measurements for the x=0 sample showed an insulating behavior and an anti-ferromagnetic (AFM) transition at 230 K as well as a charge-ordering (CO) transition at 280 K. The substitution of Cr induces a ferromagnetic-paramagnetic (FM-PM) and metal-insulator (MI) transition as well as gradually suppressing the CO state due to weakening of the Jahn-Teller (JT) effect. Quenching to reduce the oxygen content of the x=0.05 sample caused the MI transition temperature to shift to lower temperatures most likely due to oxygen reduction. On the other hand, both longitudinal and shear velocities at 100 K increased significantly with Cr substitution indicating improvement in elastic properties. However, quenching of the x=0.05 sample slightly decreased both velocities and related elastic moduli…